The mechanisms governing the activation of dislocation sources in aluminum at different strain rates. (November 2015) - Gurrutxaga-Lerma, B.; Balint, D.S.; Dini, D.; Sutton, A.P.
Abstract: This article examines the time to activate Frank–Read sources in response to macroscopic strain rates ranging from 10 1  s −1 to 10 10  s −1 in aluminium under athermal conditions. We develop analytical models of the bowing of a pinned dislocation segment as well as numerical simulations of three dimensional dislocation dynamics. We find that the strain rate has a direct influence on both the activation time and the source strength of Frank–Read sources at strain rates up to 10 6  s −1, and the source strength increases in almost direct proportion to the strain rate. This contributes to the increase in the yield stress of materials at these strain rates. Above 10 6  s −1, the speed of the bowing segments reaches values that exceed the domain of validity of the linear viscous drag law, and the drag law is modified to account for inertial effects on the motion of the dislocation. As a result the activation times of Frank–Read sources reach a finite limit at strain rates greater than 10 8  s −1, suggesting that Frank–Read sources are unable to operate before homogeneous nucleation relaxes elastic stresses at the higher strain rates of shock loading. Elastodynamic calculations are carried out to compare the contributions of Frank–Read sources and homogeneous nucleation of dislocations to plastic relaxation. We find that at strain rates of 5×10 7  s −1 homogeneous nucleation becomes the dominant generation mechanism.